Dual Function of USP14 Deubiquitinase in Cellular Proteasomal Activity and Autophagic Flux - Eunkyoung Kim; Seoyoung Park; Jung Hoon Lee; Ji Young Mun; Won Hoon Choi; Yejin Yun; Jeeyoung Lee; Ji Hyeon Kim; Min-Ji Kang; Min Jae Lee (Cell Reports, 2018)
Summary: The ubiquitin-proteasome system and the autophagy-lysosome system are two major intracellular proteolytic pathways in eukaryotes. Although several biochemical mechanisms underlying the crosstalk between them have been suggested, little is known about the effect of enhanced proteasome activity on autophagic flux. Here, we found that upregulation of proteasome activity, which was achieved through the inhibition of USP14, significantly impaired cellular autophagic flux, especially at the autophagosome-lysosome fusion step. UVRAG appeared to function as a crucial checkpoint for the proper progression of autophagic flux. Although proteasome activation through USP14 inhibition facilitated the clearance of microtubule-associated protein tau (MAPT) and reduced the amount of its oligomeric forms, the same conditions increased the formation of inclusion bodies from nonproteasomal substrates such as huntingtin with long polyglutamine repeats. Our results collectively indicate that USP14 may function as a common denominator in the compensatory negative feedback between the two major proteolytic processes in the cell. : Kim et al. present evidence that the ubiquitin-proteasome system and autophagy are in a compensatory negative-feedback connection through USP14, a proteasome-associated deubiquitinating enzyme. USP14 inhibition results in elevation of proteasome activity and facilitation of tau degradation in the cell, while it delays the cellular autophagic flux. Keywords: USP14, proteasome, ubiquitin-proteasome system, autophagy, autophagic flux, negative feedback, UVRAG, proteostasis, tau, huntingtin